DWAP 1531: An early maturing bold seeded bread wheat germplasm for warmer areas - Singh, Sanjay Kumar; Gangwar, RP; Sharma, Pradeep (Journal of Cereal Research, 2018)
Germplasm line DWAP 1531 was found promising donors for various traits especially earliness, bold seeds, and resistant to stem rust and leaf blight. This reflects its suitability to adaption in the areas experiencing a warmer climate. Thus, the genotype DWAP 1531 can be further utilized as a potential donor for these yield component traits in wheat improvement programmes.Â Â DOI:10.25174/2249-4065/2018/82263